Comparative genomics and transcriptomics of lineages I, II, and III strains of Listeria monocytogenes - Hain, Torsten; Ghai, Rohit; Billion, Andre; Kuenne, Carsten; Steinweg, Christiane; Izar, Benjamin; Mohamed, Walid; Mraheil, Mobarak; Domann, Eugen; Schaffrath, Silke; Karst, Uwe; Goesmann, Alexander; et al. (My University, 2012)
BACKGROUND: Listeria monocytogenes is a food-borne pathogen that causes infections with a high-mortality rate and has served as an invaluable model for intracellular parasitism. Here, we report complete genome sequences for two L. monocytogenes strains belonging to serotype 4a (L99) and 4b (CLIP80459), and transcriptomes of representative strains from lineages I, II, and III, thereby permitting in-depth comparison of genome- and transcriptome -based data from three lineages of L. monocytogenes. Lineage III, represented by the 4a L99 genome is known to contain strains less virulent for humans. RESULTS: The genome analysis of the weakly pathogenic L99 serotype 4a provides extensive evidence of virulence gene decay, including loss of several important surface proteins. The 4b CLIP80459 genome, unlike the previously sequenced 4b F2365 genome harbours an intact inlB invasion gene. These lineage I strains are characterized by the lack of prophage genes, as they share only a single prophage locus with other L. monocytogenes genomes 1/2a EGD-e and 4a L99. Comparative transcriptome analysis during intracellular growth uncovered adaptive expression level differences in lineages I, II and III of Listeria, notable amongst which was a strong intracellular induction of flagellar genes in strain 4a L99 compared to the other lineages. Furthermore, extensive differences between strains are manifest at levels of metabolic flux control and phosphorylated sugar uptake. Intriguingly, prophage gene expression was found to be a hallmark of intracellular gene expression. Deletion mutants in the single shared prophage locus of lineage II strain EGD-e 1/2a, the lma operon, revealed severe attenuation of virulence in a murine infection model. CONCLUSION: Comparative genomics and transcriptome analysis of L. monocytogenes strains from three lineages implicate prophage genes in intracellular adaptation and indicate that gene loss and decay may have led to the emergence of attenuated lineages.
Keywords: Listeria monocytogenes; complete genome sequences; comparative transcriptome analysis; virulence; prophage genes; ddc:610